Studi Literatur: Teknik Audit Risiko Dalam Pengungkapan Money Laundering Dari Perspektif Audit Investigatif - Dinda Hafizhoh; Tuti Meutia (Hikamatzu | Journal of Multidisciplinary, 2024)
Cases of similar fraud using the deception depicted as white-collar crime often occur. Fraud is very dangerous and detrimental to many parties, which is a conditional act. Fraud has occurred in all areas of life. Computer forensics can be used to help investigate fraud cases involving technology. The use of whistleblowers can also help uncover cover-ups. Tracing money flows or follow the money is one of the important techniques in cases of money laundering disclosure. The use of tax techniques can also be used in examining organized crime and income tax evasion. Risk-based risk management can help organizations manage potential risks and minimize potential losses. By using a risk-based audit approach and appropriate investigative audit techniques, companies can prevent and address various risks, including money laundering